The Level of Employee Trust in The Boss in The Regional Secretariat of Cirebon City - Claudia Desyosevin Ully Basa Pasaribu; Johnson Dongoran (PT Mattawang Mediatama Solution, 2022)
This study aims to identify the type of employee trust in superiors and determine the tendency of the type of employee trust in superiors. The type of this research is qualitative research that used primary data, where the researcher conducts indirect interviews in the form of open questions to 18 respondents who are employees of the Cirebon City Regional Secretariat. The data were analyzed using qualitative descriptive analysis techniques. The results showed that the dimensions of integrity, competence, consistency, and openness were mostly knowledge-based trust. Meanwhile, the loyalty dimension is at the level of identification-based trust. While the type of employee trust in superiors tends to have confidence in the level of knowledge and level of identification.